The Immunological Role of CDK4/6 and Potential Mechanism Exploration in Ovarian Cancer - Liu, Chen; Huang, Yuhan; Cui, Yaoyuan; Zhou, Jun; Qin, Xu; Zhang, Li; Li, Xi; Li, Yuan; Guo, Ensong; Yang, Bin; Li, Xi; Fan, Junpeng; et al. (Frontiers in Immunology, 2022)
Background: Ovarian cancer (OC) is one of the most lethal gynecologic cancers. Growing evidence has proven that CDK4/6 plays a key role in tumor immunity and the prognosis of many cancers. However, the expression and function of CDK4/6 in OC remain unclear. Therefore, we aimed to explore the influence of CDK4/6 in OC, especially on immunity. Methods: We analyzed CDK4/6 expression and prognosis using The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO) and Genotype Tissue Expression (GTEx) data. Subsequently, we used the cytoHubba plug-in of Cytoscape software and starBase to identify the noncoding RNAs (ncRNAs) regulating CDK4/6. Finally, we verified the effect of CDK4/6 on immunity in OC cell lines and animal models. Results: CDK4/6 expression was higher in OC tissues than in normal ovarian tissues, and the high expression levels of CDK4/6 contributed to the immunosuppressive state of OC and were thus related to the poor prognosis of OC patients. This was also in general agreement with the results of OC cell line and animal experiments. Mechanistically, the CDK4/6 inhibitor palbociclib increased the secretion of interferon (IFN)-γ and the interferon-stimulated gene (ISG) response, thereby upregulating the expression of antigen-presenting molecules; this effect was partly dependent on the STING pathway. Additionally, according to public data, the LRRC75A-AS1-hsa-miR-330-5p axis might inhibit the immune response of OC patients by upregulating CDK4/6, leading to a poor prognosis. Conclusion: CDK4/6 affects the immune microenvironment of OC and correlates with the prognosis of OC patients.